Triggering Tautomerization of Curcumin by Confinement into Liposomes. Issue 10 (27th June 2019) - Girardon, Maxime; Parant, Stéphane; Monari, Antonio; Dehez, François; Chipot, Christophe; Rogalska, Ewa; Canilho, Nadia; Pasc, Andreea
Abstract: Although solvent polarity, pH and temperature have been reported to affect the keto‐enol equilibrium of curcumin, the synergistic effect of concentration and confinement is demonstrated for the first time herein. To this end, curcumin was encapsulated into vesicles of soy lecithin of about 100 nm in diameter. The keto form is favoured in the dilute regime (up to 2 μM). Above this concentration, tautomerization is shifted towards the enol form, as shown by fluorescence and compression isotherm studies. Moreover, molecular modeling and free‐energy profiles, together with simulation of the optical properties of the curcumin isomers, allowed us to dissect the interaction of the keto and enol forms with a model membrane and confirm the concentration‐triggered tautomerization of curcumin under confinement. Abstract : Triggered tautomerisation : Curcumin was encapsulated into vesicles of soy lecithin of about 100 nm in diameter to study the synergistic effect of concentration and confinement to trigger the keto‐enol equilibrium of the molecule. The keto form is rather stabilized near the polar headgroups of the phospholipids whereas tautomerization is shifted towards the enol form in the lipid core.